2022
DOI: 10.1002/cbdv.202200053
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Shorea roxburghii Phenolic Extract on Nephrotoxicity Induced by Cyclophosphamide: Impact on Oxidative Stress, Biochemical and Histopathological Alterations

Abstract: Cyclophosphamide (CTX) is one of the most commonly used alkylating agents for the treatment of various cancers; however, CTX‐induced nephrotoxicity is one of the most prevailing side effects of the drug. Shorea roxburghii is a plant with diverse bioactivities including antioxidant, anti‐inflammatory and renoprotective effects. This study investigated the nephroprotective effect of Shorea roxburghii phenolic extract (SRPF) against CTX‐induced nephrotoxicity in rats. The rats were treated with SRPF (100 and 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It also became necessary to highlight that being important mediators and mechanisms, such as oxidative stress and inflammation, these are not renal-specific markers. Henceforth, it became permissive to estimate and evaluate the level of renal-specific injury markers such as serum creatinine (Cr), uric acid (UA), blood urea nitrogen (BUN), and various other electrolytes. , Uric acid, in normal physiology, undergoes renal excretion, and when its serum level increases beyond a certain level, it signifies compromised renal function and renal toxicity. Like uric acid, creatinine, and blood urea nitrogen also indicate the extent of healthy renal activity, and their derailed level signifies damaged renal function .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It also became necessary to highlight that being important mediators and mechanisms, such as oxidative stress and inflammation, these are not renal-specific markers. Henceforth, it became permissive to estimate and evaluate the level of renal-specific injury markers such as serum creatinine (Cr), uric acid (UA), blood urea nitrogen (BUN), and various other electrolytes. , Uric acid, in normal physiology, undergoes renal excretion, and when its serum level increases beyond a certain level, it signifies compromised renal function and renal toxicity. Like uric acid, creatinine, and blood urea nitrogen also indicate the extent of healthy renal activity, and their derailed level signifies damaged renal function .…”
Section: Discussionmentioning
confidence: 99%
“…Henceforth, it became permissive to estimate and evaluate the level of renal-specific injury markers such as serum creatinine (Cr), uric acid (UA), blood urea nitrogen (BUN), and various other electrolytes. , Uric acid, in normal physiology, undergoes renal excretion, and when its serum level increases beyond a certain level, it signifies compromised renal function and renal toxicity. Like uric acid, creatinine, and blood urea nitrogen also indicate the extent of healthy renal activity, and their derailed level signifies damaged renal function . Kidney injury molecule-1 (KIM-1) is another important and sensitive renal injury marker and has been extensively studied in various preclinical and clinical models. , Considering this fact, we also evaluated the serum levels of renal injury markers and KIM-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some parts of it have been reported that contain various a large number of effective compounds. Shorea roxburghii leaves extract has demonstrated its ability to protect against CTX-mediated kidney damage due to its antioxidant and anti-inflammatory properties [ 56 ]. Oligostilbenoids isolated from the bark of Shorea roxburghii show the anti-cancer effect in melanoma [ 48 ].…”
Section: Discussionmentioning
confidence: 99%